Increase in observed net carbon dioxide uptake by land and oceans during the past 50 years - Ballantyne, A. P.; Alden, C. B.; Miller, J. B.; Tans, P. P.; White, J. W. C. (Nature (London), 2012)
A comprehensive carbon dioxide mass balance analysis shows that net global carbon uptake has increased by about 0.05 billion tonnes per year over the past 50 years and that in that time the global carbon uptake has almost doubled, making it unlikely that land and ocean carbon sinks have decreased on a global scale. Carbon sinks hold firm The current state of land and ocean carbon sinks has been the subject of intense debate, because it has implications for how the carbon cycle might respond to climate change. About half of the current carbon dioxide emissions are taken up by land and ocean carbon sinks. Model studies predict a decline in future carbon sinks, resulting in a positive carbon-climate feedback, and several recent studies have suggested that land and ocean carbon sinks are beginning to wane. These authors use a global mass balance approach to audit the global carbon cycle, focusing on well-constrained observations of atmospheric carbon dioxide and estimates of anthropogenic emissions and a rigorous analysis of uncertainties. They find that carbon sinks have actually doubled during the past 50 years and continue to increase significantly. There were no signs, as of 2010, that carbon uptake has started to diminish on the global scale One of the greatest sources of uncertainty for future climate predictions is the response of the global carbon cycle to climate change 1 . Although approximately one-half of total CO 2 emissions is at present taken up by combined land and ocean carbon reservoirs 2 , models predict a decline in future carbon uptake by these reservoirs, resulting in a positive carbon–climate feedback 3 . Several recent studies suggest that rates of carbon uptake by the land 4 , 5 , 6 and ocean 7 , 8 , 9 , 10 have remained constant or declined in recent decades. Other work, however, has called into question the reported decline 11 , 12 , 13 . Here we use global-scale atmospheric CO 2 measurements, CO 2 emission inventories and their full range of uncertainties to calculate changes in global CO 2 sources and sinks during the past 50 years. Our mass balance analysis shows that net global carbon uptake has increased significantly by about 0.05 billion tonnes of carbon per year and that global carbon uptake doubled, from 2.4 ± 0.8 to 5.0 ± 0.9 billion tonnes per year, between 1960 and 2010. Therefore, it is very unlikely that both land and ocean carbon sinks have decreased on a global scale. Since 1959, approximately 350 billion tonnes of carbon have been emitted by humans to the atmosphere, of which about 55 per cent has moved into the land and oceans. Thus, identifying the mechanisms and locations responsible for increasing global carbon uptake remains a critical challenge in constraining the modern global carbon budget and predicting future carbon–climate interactions.